Dietary protein hydrolysates and free amino acids affect the spatial expression of peptide transporter PepT1 in the digestive tract of Atlantic cod (Gadus morhua) - Bakke, Snorre (2010)
The effects of dietary inclusions of size-fractionated peptides and free amino acids (FAAs) on Peptide Transporter 1 (PepT1) mRNA levels were assessed along the length of the intestine of juvenile Atlantic cod (Gadus morhua). Five groups of fish (10–15 g) were fed for 46 days on diets containing approximately 42% protein, provided either as fish meal (FM, control diet) or as a combination of FM with whole fish hydrolysate (FH), retenate after ultrafiltration of FH (UFR), nanofiltered retenate of FH (NFR), or a mix of FAAs, at a 30% level of FM substitution. PepT1 mRNA expression was assessed in pyloric caeca (S1) and the remainder of the intestine divided into four equally long segments (S2–S5). PepT1 transcripts were found in all segments, indicating that the whole intestine is involved in peptide absorption. Differences in the regional expression profile of PepT1 were found. Under control diet (FM diet) conditions, fish exhibited a reducedexpression in S5 compared to S2. In fish fed FAA and UFR diets, PepT1 mRNA levels were higher in S2 and S3 compared to other regions. These data suggest that PepT1 may be variably recruited along the whole intestine, including the most distal part, in response to changes in the luminal protein source content. This adaptive response might be functional to keep a maximal efficiency of protein absorption at the intestinal level.